FRI0169 DOES INITIATING TOCILIZUMAB LEAD TO BETTER DISEASE CONTROL COMPARED TO INITIATING MTX WITH LOW-MODERATE DOSE PREDNISONE IN EARLY RHEUMATOID ARTHRITIS; AN INDIRECT COMPARISON OF U-ACT-EARLY AND CAMERA-II TREAT-TO-TARGET TRIALS. (June 2019) - Verhoeven, Maxime; Tekstra, Janneke; Jacob, M; Laar, van; Bijlsma, Johannes Wj; Pethoe-Schramm, Attila; Borm, Michelle; Lafeber, Floris; Welsing, Paco
Abstract : Background: Treatment with methotrexate (MTX), often with concomitant glucocorticoids, is the cornerstone of early rheumatoid arthritis (RA) therapy. However, it may be less effective compared to (expensive) biological disease modifying anti-rheumatic drugs, such as tocilizumab (TCZ). Hitherto, the effectiveness and safety of MTX in combination with glucocorticoids have never been compared to TCZ with or without MTX. Objectives: To compare effectiveness and safety of initiating TCZ, or TCZ with MTX (TCZ+MTX) to initiation of MTX with 10mg prednisone (MTX+Pred) all in a step-up treat-to-target treatment strategy in early RA patients. Methods: Individual patient data of the U-Act-Early ( n= 317 ) and CAMERA-II ( n= 236 ) trials were used. Both were 2-year, double-blind, randomised, placebo-controlled studies evaluating step-up tight-control, treat-to-target treatment strategies with the opportunity to taper, in case of sustained remission, TCZ and/or MTX. 1, 2 Using MTX ( n=108+ 119 ) as the reference strategy, TCZ+MTX ( n= 106 ) and TCZ ( n= 103 ) were compared with MTX+Pred ( n= 117 ): primary outcome was the disease activity score (DAS28) over time. Secondary outcomes were remission, defined as DAS28<2.6, and the ConRew score (cumulative occurrence of remission and sustainment of remission). To assess the influence of acute phase reactants (APRs) on the results a disease activity outcome without APRs was also analysed (i.e. CDAI, modified due to lack of VAS physician in CAMERA-II). Multiple imputation was used for missing baseline data: HAQ, rheumatoid factor (RF) and smoking status. Multi-level models were used to account for clustering of patients within trials and for repeated measurements within patients over time. All models were corrected for baseline DAS28, HAQ, RF-status and smoking using fixed (and random) effects. Results: Differences between U-Act-Early and CAMERA-II for RF seropositivity and DAS28 at baseline were observed; respectively 73% vs. 60% (p<0.01) and 5.2 vs. 5.7 (p=0.01). DAS28 was statistically significantly lower over time for TCZ+MTX compared to MTX+Pred (mean difference: -0.62 [95%CI -1.14 to -0.10]), but not for TCZ, Table 1 . Remission occurred more often in TCZ+MTX and TCZ compared to MTX+Pred: relative risk 1.11 [95%CI 1.02 to 1.22] and 1.09 [1.00 to 1.20], respectively. ConRew scores were in line but not statistical significant different, Table 1 . When using modified-CDAI, TCZ strategies did not show better control of disease activity over time than MTX+Pred (mean difference in log transformed values: TCZ+MTX vs. MTX+Pred: 0.10 [95%CI -0.16 to 0.36]; TCZ vs. MTX+Pred: 0.24 [95%CI -0.04 to 0.52]), Table 1 . No differences in safety outcomes could be established, Table 2 . Conclusion: In early RA patients, TCZ-based strategies resulted in better DAS28 over time compared to MTX+Pred, as well as higher percentage of remission, part of these effects may be due to a specific effect of TCZ on APRs. References: [1] Bijlsma JWJ, et al. Lancet. 2016;388:343-55. [2] Bakker MF, et al. Ann Intern Med. 2012;156:329-339. Disclosure of Interests: Maxime Verhoeven: None declared, Janneke Tekstra: None declared, Jacob M. van Laar Grant/research support from: Genentech, Consultant for: F. Hoffmann-La Roche, Johannes WJ Bijlsma Grant/research support from: The department of the author who included patients (JWJB) in the U-Act-Early trial received reimbursements from Roche Nederland BV. JWJB reported grants and fees from Roche, AbbVie, Bristol-Myers Squibb, Merck Sharp & Dohme, Pfizer, and UCB University Medical Center Utrecht, Utrecht University, Consultant for: SUN Pharma, Speakers bureau: Lilly, Roche, Attila Pethoe-Schramm Shareholder of: F. Hoffmann-La Roche, Employee of: F. Hoffmann-La Roche, Michelle Borm Employee of: An employee of Roche Nederland BV, Floris Lafeber Shareholder of: ArthroSave, Grant/research support from: FOREUM; Dutch Arthritis Society, Paco Welsing: None declared